Magnetotransport properties of noncentrosymmetric CaAgBi single crystal - Sasmal, Souvik; Mondal, Rajib; Kulkarni, Ruta; Thamizhavel, Arumugam; Singh, Bahadur (Journal of physics. Condensed matter, 2020)
We report on the single crystal growth and transport properties of a topological semimetal CaAgBi which crystallizes in the hexagonal ABC-type structure with the non-centrosymmetric space group 6 (No. 186). The transverse magnetoresistance measurements with current in the basal plane of the hexagonal crystal structure reveal a value of about 30% for ∥[10̄0] direction and about 50% for ∥[1̅10] direction at 10 K in an applied magnetic field of 14 T. The magnetoresistance shows a cusp-like behavior in the low magnetic field region, suggesting the presence of weak antilocalization effect for temperatures less than 100 K. The Hall measurements reveal that predominant charge carriers are p-type, exhibiting a linear behavior at high fields. The magnetoconductance of CaAgBi is analyzed based on the modified Hikami-Larkin-Nagaoka model. Our first-principle calculations within a density-functional theory framework reveal that the Fermi surface of CaAgBi consists of both the electron and hole pockets and the size of the hole pocket is much larger than electron pockets suggesting the dominant p-type carriers in accordance with our experimental results.